The Evolution of Corporate Ownership after IPO: The Impact of Investor Protection - Foley, C. Fritz; Greenwood, Robin (Review of Financial Studies, 2010)
Panel data on corporate ownership in thirty-four countries between 1995 and 2006 reveal that newly public firms have concentrated ownership regardless of the level of investor protection. After listing, firms in countries with strong investor protection are more likely to experience decreases in ownership concentration; these decreases occur in response to growth opportunities, and they are associated with new share issuance. We conclude that ownership concentration falls after listing in countries with strong investor protection, because firms in these countries continue to raise capital and grow, diluting blockholders as a consequence.